A novel function for transglutaminase 1: Attachment of long-chain ω-hydroxyceramides to involucrin by ester bond formation - Nemes, Zoltán (The National Academy of Sciences, 1999)
Transglutaminases (TGases) are defined as enzymes capable of forming isopeptide bonds by transfer of an amine onto glutaminyl residues of a protein. Here we show that the membrane-bound form of the TGase 1 enzyme can also form ester bonds between specific glutaminyl residues of human involucrin and a synthetic analog of epidermal specific ω-hydroxyceramides. The formation of a ≈5-nm-thick lipid envelope on the surface of epidermal keratinocytes is an important component of normal barrier function. The lipid envelope consists of ω-hydroxyceramides covalently linked by ester bonds to cornified envelope proteins, most abundantly to involucrin. We synthesized an analog of natural ω-hydroxyceramides N-[16-(16-hydroxyhexadecyl)oxypalmitoyl]sphingosine (lipid Z). When recombinant human TGase 1 and involucrin were reacted on the surface of synthetic lipid vesicles containing lipid Z, lipid Z was attached to involucrin and formed saponifiable protein–lipid adducts. By mass spectroscopy and sequencing of tryptic lipopeptides, the ester linkage formation used involucrin glutamine residues 107, 118, 122, 133, and 496 by converting the γ-carboxamido groups to lipid esters. Several of these residues have been found previously to be attached to ceramides in vivo. Mass spectrometric analysis after acetonide derivatization also revealed that ester formation involved primarily the ω-hydroxyl group of lipid Z. Our data reveal a dual role for TGase 1 in epidermal barrier formation and provide insights into the pathophysiology of lamellar ichthyosis resulting from defects of TGase 1 enzyme.